Prevalence and pattern of social media use and its effect on social health among Fayoum university students - Masoud, Mohamed; Abdeltaweb, Ahmed K.; Abd Elmonem, Mohamed; Masoud, Ahmed T.; Mohammed, Omar M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Social media social media are caused a revolution in the last century. Almost everyone has access to social media with different ways. Many students use Social media for contact with each other, following updating news, and help them in their study. The study aimed to estimate the prevalence, pattern of Social media and its effects on social health of Fayoum university students. Methods: This is a cross-sectional descriptive study involving 633 students at Fayoum university. Results: As regards social media use, the majority of the student (94.2%) was using at least one type of SM. More than half of them (55.5%) visit (3-5) SM sites. About one third of the students (30.9%) stated that they spend (3-4) hours daily. Regarding effect of social media, one third of the students (30.2%) thought that SM sites decrease friendship level, (73.0%) limit sport time, and has a negative effect on the learning process (62.4%). The motivations for using social media were the search for news (38.1%) and making friendship (31.2%). Multiple logistic regression for factors associated with using social media revealed that age more than 20 years and male gender were significantly associated with using social media (p=0.003 and 0.016, respectively). Conclusions: The majority of students use Social media for different reasons. Social media reduced social interrelations of the students may set down their study. So, increase awareness about the hazards of social media among students including their physical and psychosocial health. Highlighted the balanced use of social media for proper improving the learning process through prompt uses of information and communication.